XI2S-IDS: An Explainable Intelligent 2-Stage Intrusion Detection System - Maiada M. Mahmoud; Yasser Omar Youssef; Ayman A. Abdel-Hamid (Future Internet)
The rapid evolution of technologies such as the Internet of Things (IoT), 5G, and cloud computing has exponentially increased the complexity of cyber attacks. Modern Intrusion Detection Systems (IDSs) must be capable of identifying not only frequent, well-known attacks but also low-frequency, subtle intrusions that are often missed by traditional systems. The challenge is further compounded by the fact that most IDS rely on black-box machine learning (ML) and deep learning (DL) models, making it difficult for security teams to interpret their decisions. This lack of transparency is particularly problematic in environments where quick and informed responses are crucial. To address these challenges, we introduce the XI2S-IDS framework—an Explainable, Intelligent 2-Stage Intrusion Detection System. The XI2S-IDS framework uniquely combines a two-stage approach with SHAP-based explanations, offering improved detection and interpretability for low-frequency attacks. Binary classification is conducted in the first stage followed by multi-class classification in the second stage. By leveraging SHAP values, XI2S-IDS enhances transparency in decision-making, allowing security analysts to gain clear insights into feature importance and the model’s rationale. Experiments conducted on the UNSW-NB15 and CICIDS2017 datasets demonstrate significant improvements in detection performance, with a notable reduction in false negative rates for low-frequency attacks, while maintaining high precision, recall, and F1-scores.